2017
DOI: 10.1038/srep45759
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced methane emissions from tropical wetlands during the 2011 La Niña

Abstract: Year-to-year variations in the atmospheric methane (CH4) growth rate show significant correlation with climatic drivers. The second half of 2010 and the first half of 2011 experienced the strongest La Niña since the early 1980s, when global surface networks started monitoring atmospheric CH4 mole fractions. We use these surface measurements, retrievals of column-averaged CH4 mole fractions from GOSAT, new wetland inundation estimates, and atmospheric δ13C-CH4 measurements to estimate the impact of this strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 59 publications
5
59
1
Order By: Relevance
“…However, according to Figure 2b this zonal anomaly can be explained largely by transport, as found in our global analysis already. This finding is consistent with increased wetland emissions in the Northern Tropics reported by Pandey et al (2017). This is consistent with the hypothesis of Nisbet et al (2016) that emissions in the Southern Tropics were enhanced during 2014 as it was an exceptionally warm and wet year in Southern Africa and Amazonia.…”
Section: Zonal Growth Ratessupporting
confidence: 91%
“…However, according to Figure 2b this zonal anomaly can be explained largely by transport, as found in our global analysis already. This finding is consistent with increased wetland emissions in the Northern Tropics reported by Pandey et al (2017). This is consistent with the hypothesis of Nisbet et al (2016) that emissions in the Southern Tropics were enhanced during 2014 as it was an exceptionally warm and wet year in Southern Africa and Amazonia.…”
Section: Zonal Growth Ratessupporting
confidence: 91%
“…Specifically, the 0.8 ppm step-like increase in this difference between 2009 and 2010 was attributed to the opening and closing of the upper-tropospheric equatorial westerly duct (Waugh and Funatsu, 2003), with an open-duct pattern from July 2008 to June 2009 (fast IH exchange), followed by closed-duct conditions from July 2009 to June 2010 (slow IH exchange). Confirming this mechanism, Pandey et al (2017) also found faster IH transport of CH 4 during the strong La Niña in 2011 using the TM5 CTM. The timescale of IH transport is an important parameter for atmospheric inversion studies.…”
Section: Introductionmentioning
confidence: 48%
“…Natural emissions would be reduced under sulfate geoengineering for three main reasons: (1) a reduction in surface temperatures that would, in turn, be connected with a highly probable reduction in rainfall, compared with the predicted increase under most future warming scenarios (Trenberth, 1998;Pandey et al, 2017); this would reduce the amount of CH 4 produced by wetland areas, thus affecting the atmospheric methane concentration; (2) the increased surface deposition of sulfate under SG conditions would itself produce changes in emissions from wetlands (Gauci et al, 2008); (3) SG could help avert one of the possible risks of global warming, i.e., the emission of methane from permafrost thawing (Kohnert et al, 2017). It remains to be investigated how much these effects, together, could offset the photochemical CH 4 increase resulting from our study.…”
Section: Discussionmentioning
confidence: 99%